Corruption and tax noncompliance variables: An empirical investigation from Yemen - Obaid, Mohammed Mahdi; Mat Udin, Noraza (Sciedu Press, 2020)
Tax revenue is an important source of income for various governments around the world. However, challenges, as a result of corruption and tax noncompliance behaviour among the taxpayers, are hindering the adequate generation of such revenues for the government. The objective of this study is to investigate the effect of corruption and other tax noncompliance variables on tax revenue generation in Yemen. The study used survey research design via a questionnaire to collect data from 264 individual taxpayers in the Hadhramout Governorate. The collected data was analyzed using SPSS to perform reliability test, descriptive statistics, multicollinearity test, and regression analysis. The findings of the study show that corruption and tax rate are positively related to tax noncompliance; income level is negatively related to tax noncompliance; whereas penalty rate and education level are positive but not related to tax noncompliance. The implication of the study is that the government and the tax authority should update and institute new tax laws and policies that could minimize corruption among their officials and create more awareness among the taxpayers on the importance of paying tax to the government, so as to increase their compliance behaviour